An Analysis Psychology of Trauma Toward The Main Character in The Midsommar Movie by Ari Aster - Murtadho, Abdul Muhid; Dirmansyah, Firmansyah; Sitepu, Julyanta Br (JELL (Journal of English Language and Literature) STIBA-IEC Jakarta, 2025)
This research focuses on criticizing the problem that happened related to Psychology of Trauma. The purposes of this research are to find out the types and the impact of Psychology of Trauma toward the main character in the Midsommar movie. In this research, the writer used the method of content analysis, which is a form of qualitative research. The data were collected through transcript (words, dialogue, sentences, and scenes) of the movie as unit analysis. The data were analyzed by classifying, categorizing, and coding the themes. After that, the data were interpreted based on the perspective of the writer. The results showed that the Midsommar movie contained psychology trauma toward Dani (Main character) in the movie. First: two types of Anxiety consist Second: three types of psychotic disorder. The Last: six types of Human-Caused Trauma. The results analysis showed that the Type of Human-Caused Trauma was dominant in the Midsommar movie.